Cell wall disassembly during papaya softening: Role of ethylene in changes in composition, pectin-derived oligomers (PDOs)production and wall hydrolases - Sañudo-Barajas, J.A.; Labavitch, J.; Greve, C.; Osuna-Enciso, T.; Muy-Rangel, D.; Siller-Cepeda, J.
Cell wall disassembly in ripening climacteric fruit is a highly complex process where ethylene plays a crucial role. Ethylene inhibitors can be used to explore the changes in the cell wall matrix and crosslinked polysaccharides in ethylene-regulated processes. The results of applying the ethylene receptor blocking inhibitor 1-methylcyclopropene (1-MCP)and the ethylene-releasing compound ethephon (2- chloroethylphosphonic acid)indicate that softening of 'Maradol' papaya fruit is dependent on ethylene. When fruit were induced to ripen extensively by exposure to a high dose of ethephon, 1-MCP inhibited the subsequent softening dramatically, but when inhibition of the ethylene response was caused by application of 1-MCP, subsequent fruit treatment with ethephon promoted extensive loss of galactose from the water-soluble polysaccharides, but this was not accompanied by fruit softening. The cell wall changes accompanying normal fruit softening were pectin solubilization and polyuronide depolymerization and these processes occurred simultaneously. Polygalacturonase likely is responsible for the ripening-associated changes in 'Maradol' papaya fruit texture and pectin polymer integrity. An increase in extractable fruit polygalacturonase follows the increased presence of pectin-derived oligosaccharides.
Keywords: CARICA PAPAYA; FRUIT SOFTENING; 1-METHYLCYCLOPROPENE; ETHEPHON; POLYSACCHARIDES